Experimental study on heat energy recovery and utilization of coal gangue hill based on gravity heat pipe. (October 2022) - Peng, Hong; Jia, XiangLong
Abstract: The coal gangue hill is formed by the accumulation of waste in the coal mining process. A large amount of heat energy accumulates inside it, which makes it prone to spontaneous combustion, seriously pollutes the environment and wastes resources. In this paper, taking a gangue hill in a mining area as an example, a gravity heat pipe device is used to extract heat from the deep part of the gangue hill, and a mathematical model for heat extraction is established. And through experiments to explore the cooling effect of coal gangue at different depths, it is concluded that the cooling range of gravity heat pipe can reach about 15%. At the same time, to avoid the waste of geothermal resources, this paper uses the extracted heat twice and designs a thermoelectric power generation system based on the gravity heat pipe device to realize the purpose of resource utilization of the underground heat energy of coal gangue hills. The experimental results show that the thermoelectric conversion efficiency can reach 7.39%, and after the addition of the soaking plate, the thermoelectric efficiency is increased to 9.02%, which has a very important reference significance for promoting the treatment of coal gangue hills and the recovery and utilization of low-temperature geothermal heat.